Assistive tools towards personal learning environment in higher education - Nooralisa Mohd Tuah; Dg Senandong Ajor; Nuraini Jamil (International Association of Computer Science and Information Technology Pres, 2015)
This study explores the tools and materials used in personal learning environment (PLE) by investigating the impact of embedding a mashup technology into learning environment. With Web 2.0 technologies, mashing up several materials into learning repository helps learners to form their own scope of learning. A PLE mashup model is suggested in determining suitable tools and materials. Based on the current trends in Web 2.0, another aspect of PLE that could be further investigated is the adoption of social media application for formal higher education level. A study on student perception shows a positive acceptance towards PLE in their learning activities. In order to serve as learning tool, how the technology could be implemented, and its limitation towards efficiency was highlighted.